Equilibrium Policy Experiments and the Evaluation of Social Programs - Jeremy Lise; Shannon Seitz; Jeffrey Smith (Queen's University, Department of Economics, 2005)
In this paper we provide new and convincing evidence on the presence and magnitude of feedback effects associated with 'make work pay' policies currently under consideration in the US, Canada, the UK and other developed countries. We build a general equilibrium model of the labor market and use the model to study the effects of policies currently implemented in practice only as small-scale social experiments. The evidence from our model experiments is particularly compelling as we first test the partial equilibrium implications of our model using experimental data: in particular, we calibrate the model to the control group in a randomized experiment and find the model predicts the program group outcomes and the experimental impact estimates very well. We then use the model to quantify the effects of the experimental program introduced in general equilibrium. We apply our methodology to the evaluation of the Canadian Self-Sufficiency Project (SSP), a policy providing generous financial incentives for Income Assistance (IA) recipients to obtain stable employment. Our results reveal several important feedback effects associated with the SSP policy; taken together, these feedback effects reverse the cost-benefit conclusions implied by the partial equilibrium experimental evaluation. The substantial general equilibrium effects reported here are illustrative of the feedback effects that are likely to arise in a broad range of other programs that seek to 'make work pay' through the subsidization of search and work.
Keywords: J2; I38; J6; 330; Program evaluation; policy experiments; Self-Sufficiency Project; welfare; social experiments; equilibrium search models